The ability of free to total prostate-specific antigen and prostate-specific antigen density to detect clinically significant prostate cancer in men undergoing transperineal template biopsy. (November 2017) - Segaran, Surayne V; Emara, Amr M; Mahesan, Tharani; Silverman, Joshua; Ahmed, Hashim U; Bott, Simon RJ; Hindley, Richard G
Objective: The purpose of this study was to determine the ability of the ratio of free to total prostate-specific antigen and prostate-specific antigen density to predict the presence of clinically significant prostate cancer on template biopsies. The value of these tests may be underestimated as they were previously validated against sextant transrectal biopsy of the prostate, which has been proved to miss a large proportion of significant prostate cancers. The ability of these tests to specifically detect clinically significant cancers has not previously been studied. Patients and methods: A retrospective analysis was performed of patients undergoing transperineal template biopsy who also had free to total prostate-specific antigen and prostate-specific antigen density. Receiver-operating characteristic analysis was performed to determine the comparative utility of each test in the detection of all cancers as well as clinically significant cancers, by means of the area under the curve. Results: Data from 293 patients were analysed. Prostate cancer was detected in 72% of patients, of which 62% of this group had clinically significant disease. Receiver-operating characteristic analysis demonstrated the superiority of prostate-specific antigen density and free to total prostate-specific antigen over standard prostate-specific antigen in the overall detection of cancer (area under the curve 0.662 and 0.674 vs 0.534, p =0.003 and 0.02 respectively). Both tests were even more effective in the detection of clinically significant cancers (area under the curve 0.755 and 0.715 vs 0.572, p <0.0001 and 0.009 respectively). Conclusion: The free to total prostate-specific antigen and prostate-specific antigen density both appear to perform well at detecting clinically significant prostate cancer in our population of men undergoing template biopsy. The potential role of these inexpensive tests should not be overlooked as they may be of value when deciding which patients require biopsy following an initial magnetic resonance imaging scan and also for those on surveillance protocols.